2017
DOI: 10.1002/jbio.201700097
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3‐dimensional tissue lung phantom of a preterm infant for optical measurements of oxygen—Laser‐detector position considerations

Abstract: There is a need to further improve the clinical care of our most vulnerable patients-preterm infants. Novel diagnostic and treatment tools facilitate such advances. Here, we evaluate a potential percutaneous optical monitoring tool to assess the oxygen and water vapor content in the lungs of preterm babies. The aim is to prepare for further clinical studies by gaining a detailed understanding of how the measured light intensity and gas absorption signal behave for different possible geometries of light deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The the ey wavelengths SMAS has been avities like sinu ed is to develop ng GASMAS which promp 0 nm ( Fig. 3( [11], [34]. Th pted us to choo a), 3(b)), a tab broadband ran with well char characterized o ttering 5-25 cm is range that w ompute: Figure 3(c), 3(d) illustrate the dependency of reduced scattering coefficient on absorber concentration and vice versa.…”
Section: Instrumementioning
confidence: 99%
See 1 more Smart Citation
“…The the ey wavelengths SMAS has been avities like sinu ed is to develop ng GASMAS which promp 0 nm ( Fig. 3( [11], [34]. Th pted us to choo a), 3(b)), a tab broadband ran with well char characterized o ttering 5-25 cm is range that w ompute: Figure 3(c), 3(d) illustrate the dependency of reduced scattering coefficient on absorber concentration and vice versa.…”
Section: Instrumementioning
confidence: 99%
“…We have pre documented p simultaneousl relevant to hu reliable nature than 4% whic of 5% was o recipe could [11,31].…”
Section: Conclusiomentioning
confidence: 99%
“…The 3D printing of lung and thorax phantoms has been described before. 2,[14][15][16][17] Jung et al created lung subvolumes with a cylindrical shape to fit into a commercial phantom. 2 They used polylactic acid (PLA, density 1.25 g/cm³) to print lung tissue and the volume that is presumably air inside the lung was filled with 0.3 mm strips as a supporting structure.…”
Section: Introductionmentioning
confidence: 99%
“…The signal amplitude at different source‐detector distances must be considered. Experimentally we have found that GASMAS measurement have reached the signal‐to‐noise limit at a signal amplitude at a level of about 10 −6 of the injected light power) . The precise threshold in the detected signal amplitude would obviously depend on the performance of the detection system, for example, the utilized components and the resulting optical noise of the actual GASMAS measurements.…”
Section: Simulationmentioning
confidence: 99%
“…To do this, computed tomography (CT) images of premature infants have been used to construct three‐dimensional (3D) computer models of the thorax of these infants. Such a computer model was employed to create a 3D printed physical phantom, on which possible geometries for GASMAS measurements of lung oxygen concentration were experimentally investigated, as described in a recent paper by our group . In the present work a simulation based light transport model is instead developed.…”
Section: Introductionmentioning
confidence: 99%